Value Chain Analysis to Improve Competitive Advantage Using VRIO at RM Bu Tomo Slawi, Tegal - Wildan Hilmi; Nandang, Nandang; Ismail Yusuf (SEAN Institute, 2024)
Indonesia's culinary diversity is one of the richest in the world. Satay is one of the original foods originating from Indonesia. Goat satay is a speciality food originating from Tegal, Central Java. The number of restaurants that provide goat satay in Tegal requires each business to have a strategy in order to achieve competitive advantage. The purpose of this research is to analyse RM Bu Tomo Slawi, Tegal in order to achieve competitive advantage using value chain and VRIO analysis. This research uses a qualitative case study method with data collection techniques. The results show that some activities, such as procurement, operations, and inbound logistics, have provided a competitive advantage. However, there are weaknesses in other activities, such as firm infrastructure, technology development, marketing and sales, and service, which are not fully optimised in supporting competitive advantage.